Effect Of Raw Material Variation On Briquette Quality - Moh Binar; Muanah Muanah; Muliatiningsih Muliatiningsih (Universitas Muhammadiyah Mataram, 2021)
The main source of energy for humans is natural resources derived from fossils. Scarcity and rising oil prices will continue to occur due to its non-renewable nature. This must be immediately balanced with the provision of alternative energy sources that are renewable, abundant and cheap so that they are affordable by the wider community. The use of briquettes is based on the increasing price of petroleum in the global market. Charcoal briquettes are charcoal that is further processed into briquettes (special and more attractive appearance) that can be used for daily purposes. This study aims to determine the best raw materials in making quality briquettes. The method used in this research is an experimental method with experiments in the laboratory. The design used is a completely randomised design (CRD) consisting of 5 treatments as follows, P1: 100% corn cob, P2: 75% corn cob + 25% rice husk, P3: 50% corn cob + 50% rice husk, P4: 25% corn cob +75% rice husk and P5: 100% rice husk. Observation data were analysed using Anova (analysis of variance) at the 5% level. If there is a significant difference, then it is continued with the honest real difference test (BNJ) at the real level of 5%. The lowest value of water content was P5 which was 47.44%, in the stability of the smallest shape change was P1 4.0%, the least particle loss was P1 0.35% and the longest burning time was P3 at 113 minutes. Based on the research results, the best treatment is P3 where the moisture content value is 47.64%, with particle loss of 0.77%, and the longest burning time is 113 minutes.